Pemertahanan Bahasa Bali di Banjar Anyar Kelod Kelurahan Kerobokan Kuta Utara Kabupaten Badung - Kerianta, I Wayan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The progress of the tourism industry in Bali has gained recognition both nationally and internationally. The proximity of an area to tourist destinations naturally influences the social status of the local community. The social conditions of such communities also affect the residents’ proficiency in using the Balinese language. In this context, the researcher conducted a study to examine the maintenance of the Balinese language in Anyar Kelod, Kerobokan Village, North Kuta District, Badung Regency. This study employed a qualitative approach. The data were obtained from the local community through observation and interview techniques. The collected data were analyzed through several stages, namely data reduction, data presentation, and conclusion drawing. The findings indicate that the Balinese language is still used within the Anyar Kelod community, Kerobokan Village, North Kuta District, Badung Regency. However, further efforts are needed to enhance the community’s Balinese language proficiency. Various initiatives have been undertaken to address challenges in language maintenance, one of which is the annual celebration of the Balinese Language Month (Bulan Bahasa Bali).